Gynaecological causes of abdominal pain. Issue 5 (May 2018) - Body, Samantha; Phillips, Christian
Abstract: Abdominal pain is a common presentation both in the acute and outpatient setting. It poses a diagnostic challenge as differential diagnosis can be exhaustive. This article aims to cover differences in history, examination and investigations when considering gynaecological reasons for abdominal pain and the common causes of pain in both pregnancy and the non-pregnant female, which will be useful to a surgical trainee.